GIRLS' PERCEPTIONS OF FAMILY LIFE AND ETHNIC STEREOTYPES (Universal International Scientific Journal, 2026)
This article is a theoretical study of the concept of family and its representation in the imagination of Uzbek and Kyrgyz girls from a national-psychological perspective. The results of a socio-psychological survey conducted to determine the ethnopsychological characteristics of family values ​​are also analyzed.
Keywords: Sexual and legal maturity, physiological maturity, family-marital relations, upbringing in the family, family values, honesty in the family, relationships in the family.